Glucocorticoids Equally Stimulate Epithelial Na(+) Transport in Male and Female Fetal Alveolar Cells - Laube, Mandy (Int J Mol Sci, 2019)
Preterm infants frequently suffer from respiratory distress syndrome (RDS), possibly due to lower expression of epithelial Na(+) channels (ENaC). RDS incidence is sex-specific, affecting males almost twice as often. Despite the use of antenatal glucocorticoids (GCs), the sex difference persists. It is still controversial whether both sexes benefit equally from GCs. We previously showed that Na(+) transport is higher in female compared with male fetal distal lung epithelial (FDLE) cells. Since GCs increase Na(+) transport, we hypothesized that their stimulating effect might be sex-specific. We analyzed FDLE cells with Ussing chambers and RT-qPCR in the presence or absence of fetal serum. In serum-free medium, GCs increased the ENaC activity and mRNA expression, independent of sex. In contrast, GCs did not increase the Na(+) transport in serum-supplemented media and abolished the otherwise observed sex difference. Inhibition of the GC receptor in the presence of serum did not equalize Na(+) transport between male and female cells. The GC-induced surfactant protein mRNA expression was concentration and sex-specific. In conclusion, female and male FDLE cells exhibit no sex difference in response to GCs with regard to Na(+) transport, and GR activity does not contribute to the higher Na(+) transport in females.